Peningkatan Kesadaran Masyarakat Terhadap Kebersihan Lingkungan Melalui Sosialisasi Pemilahan dan Pengolahan Sampah di Desa Mengok, Kecamatan Pujer, Kabupaten Bondowoso - Nur Hisamuddin; Muhammad Faqih Hakim; Laurentia Florella Mulyadi; Siti Fitriyati Muzayyanah; Adhimatur Rohma Salsabila; Regyta Nuraini; Umi Nur Laili; Prudence Adhiba Pramesti Sukokaryo; Mega Juli Yati; Muhammad Wahyu; Mochammad Dwi Rizky (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
In 2020, Indonesia is ranked as the fifth largest waste producing country in the world after Brazil, India, America, and China. Poor waste management, especially by allowing it to accumulate without proper handling, can cause various problems such as health problems resulting from the presence of hazardous materials and chemicals in waste. Providing knowledge about how to sort and process waste, especially to village communities, is quite important because it is to preserve the environment, especially in villages, to solve waste problems in villages. The purpose of this KKN activity is to raise public awareness of the environment. The method of implementing the activity is in the form of observation to look for problems in Mengok Village and carrying out socialization activities on waste sorting and processing with the waste bank.